2021
DOI: 10.1016/j.jjcc.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the flood disaster caused by the Reiwa first year east Japan typhoon and cardiovascular and cerebrovascular events in Nagano City: The SAVE trial

Abstract: Background: The Reiwa First Year East Japan Typhoon of 2019 caused a torrential flood in Japan. In Nagano City, a large area was flooded due to the collapse of the Chikuma River embankment. After largescale disasters, an increase in cardiovascular and cerebrovascular events has been reported on account of the stressful conditions. However, few reports of disaster-related diseases associated with flood damage have been described. Thus, our aim was to elucidate the effect of floods on the incidences of cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…CVD reports increased in primary care and emergency departments at various locations in Hawaii after Hurricane Iniki in 1992 in comparison with prehurricane primary care visits [relative risk (RR) 2.73; 95% CI: 1.51, 4.94] prior to landfall. 57 After the Reiwa East Japan Typhoon, 69 MI-related hospitalizations significantly increased up to 2 months after landfall, and stroke hospitalizations increased 2 wk after landfall in comparison with stroke hospitalizations in prior years. After Hurricane Harvey, intensive care admissions related to worsened heart failure and CHD represented 15% of intensive care unit (ICU) cases related to hurricane flooding, although it was unclear whether this represented a deviation from prehurricane norms.…”
Section: Resultsmentioning
confidence: 98%
“…CVD reports increased in primary care and emergency departments at various locations in Hawaii after Hurricane Iniki in 1992 in comparison with prehurricane primary care visits [relative risk (RR) 2.73; 95% CI: 1.51, 4.94] prior to landfall. 57 After the Reiwa East Japan Typhoon, 69 MI-related hospitalizations significantly increased up to 2 months after landfall, and stroke hospitalizations increased 2 wk after landfall in comparison with stroke hospitalizations in prior years. After Hurricane Harvey, intensive care admissions related to worsened heart failure and CHD represented 15% of intensive care unit (ICU) cases related to hurricane flooding, although it was unclear whether this represented a deviation from prehurricane norms.…”
Section: Resultsmentioning
confidence: 98%
“…The results of a study in 2021 in Japan to explore the rate of DVT among flood victims between 2017 and 2019 showed that the DVT rate did not have an ascending trend; various factors including place of residence of the evacuees who had been away from the destructive regions as well as active DVT screening have been among the reasons of this non-ascending trend. 38 Also, the results of another study in the United States showed that tornado had no effect on increasing the rate of DVT. 39 Comparative examination of the studies shows that the results of the performed studies have not been line with the present study, and DVT trend has been ascending in earthquake, while not being increasing in other natural disasters.…”
Section: Discussionmentioning
confidence: 98%
“… 35 , 36 , 37 , 38 Natural disasters and extreme weather events Flooding events are associated with an increase in prescription medication access, cardiovascular and cerebrovascular cases, and cognitive decline in older adults. Potential cascading events and complex disasters with exacerbating impacts of climate change High degree of uncertainty regarding these exogenous shocks 39 , 40 , 41 Unprecedented global health crises The COVID-19 pandemic has impacted temperature-related health outcomes in Japan, potentially due to precautionary measures that have altered human behavior. N/A 42 , 43 , 44 Legend Significance Urgency Confidence Recognized as having particularly significant impacts High High Recognized as having impacts Medium Medium — N/A c Low Low — N/A c — N/A c a The impact assessments regarding significance, urgency, and confidence for the first five categories—heat-related illness, cold-related deaths, water-borne and food-borne diseases, vector-borne diseases, and complex impacts of air pollution (O 3 ) and warming—were adapted from the government's Assessment Report on Climate Change impacts in Japan based on the evaluations by government experts.
…”
Section: Climate Change and Impact On Healthmentioning
confidence: 99%